The impact of house prices on pension saving in early adulthood - Rowena Crawford; Polly Simpson (Institute for Fiscal Studies (IFS), 2020)
In this paper, we estimate the effect of house prices on whether or not young adults actively save in a private pension. We use job-level data from a survey of employers, matched to average house prices at the level of an individuals' location of employment, exploiting geographical variation in local house price movements in England over the decade 1997 to 2007. We find that after controlling for individual and job characteristics there is no statistically significant effect, on average, across all employees. There is a negative effect for public-sector workers and those in the middle of the earnings distribution. However, the effects are small - for example, among public-sector workers, if house prices are 100,000 higher, then this is associated with a 3 percentage point lower probability of contributing to a pension. The effect is larger among employees in the NHS, education and non-uniformed services, who face a higher employee contribution than employees in the civil service.
Keywords: D14; D15; 330; Immobilienpreis; Wirkungsanalyse; Private Altersvorsorge; Berufsgruppe; Beschäftigungsstruktur; Öffentlicher Sektor; Privatwirtschaft; IV-Schätzung; England